Genetic deletion of the 67‐kDa isoform of glutamate decarboxylase alters conditioned fear behavior in rats. Issue 2 (30th December 2020) - Fujihara, Kazuyuki; Sato, Takumi; Miyasaka, Yoshiki; Mashimo, Tomoji; Yanagawa, Yuchio
Abstract : The GABAergic system is thought to play an important role in the control of cognition and emotion, such as fear, and is related to the pathophysiology of psychiatric disorders. For example, the expression of the 67‐kDa isoform of glutamate decarboxylase (GAD67), a GABA‐producing enzyme, is downregulated in the postmortem brains of patients with major depressive disorder and schizophrenia. However, knocking out the Gad1 gene, which encodes GAD67, is lethal in mice, and thus, the association between Gad1 and cognitive/emotional functions is unclear. We recently developed Gad1 knockout rats and found that some of them can grow into adulthood. Here, we performed fear‐conditioning tests in adult Gad1 knockout rats to assess the impact of the loss of Gad1 on fear‐related behaviors and the formation of fear memory. In a protocol assessing both cued and contextual memory, Gad1 knockout rats showed a partial antiphase pattern of freezing during training and significantly excessive freezing during the contextual test compared with wild‐type rats. However, Gad1 knockout rats did not show any synchronous increase in freezing with auditory tones in the cued test. On the other hand, in a contextual memory specialized protocol, Gad1 knockout rats exhibited comparable freezing behavior to wild‐type rats, while their fear extinction was markedly impaired. These results suggest that GABA synthesis by GAD67 has differential roles in cued and contextual fear memory. Abstract : Inhibitory neurotransmitter GABA is synthesized by two enzymes, the glutamate decarboxylase 67‐kDa isoform (GAD67) and the 65‐kDa isoform (GAD65). Knocking out the Gad1 gene, which encodes GAD67, is lethal in mice, and therefore, the association between Gad1 and emotional function was unclear. In the present study, we assessed the impact of Gad1 knockout on fear expression and fear memory for the first time, using newly generated knockout rats.